Types of the nasal septum deviations and their influence on the state of mucociliary clearance of the nasal cavity in patients with postnasal obstruction syndrome - Didkovskiy, Viaheslav; Shevchuk, Yuriy; Konovalov, Serhii (ScienceRise: Medical Science, 2023)
The flow of nasal secretions into the pharynx and larynx manifests itself differently throughout the day. At night, this mucus flows into the larynx, irritates reflexogenic zones and causes coughing, and during the day these complaints are less noticeable, due to involuntary swallowing of secretions. We hypothesized that different types of nasal septum deviations may affect mucociliary clearance and, as a result, lead to postnasal drip syndrome. However, we did not find any studies in the literature that examined the effect of types of nasal septum deviation (NSD) on mucociliary clearance (MCC). Therefore, in our study, we evaluated the effect of the types of nasal septum deviations on MCC. The aim of the study. To investigate the activity of mucociliary clearance of the mucous membrane of the nasal cavity in patients with different types of NSD. Materials and methods. 100 patients were investigated. All patients underwent an endoscopic examination of the nasal cavity, a ST scan of the nasal cavity, and a saccharin test. The results. The analysis made it possible to reveal that in most patients with type 2 deviation of the nasal septum with the presence of a unilateral caudal ridge, which cuts into the middle turbinate, there is PNDS. At the same time, while the average ST time of the concave side of the nasal mucosa in patients with type 1 was almost unchanged, it was significantly longer in patients with type 2 (P=0,02). Therefore, in this study, the ST indicator in min. was longer on the concave side of the nasal cavity than on the convex side. Conclusions. Our research has shown that nasal septum deviation reduces nasal mucociliary activity, and this effect can be easily assessed using the saccharin test. According to our observations and research results, it was the 2nd and 3rd types of deviation that significantly disturbed the architecture of the nasal cavity, due to the presence of contralateral vertical deviation of the nasal septum, contralateral hyperplasia of the nasal turbinates, and contralateral conchobulosis. And, as a result, led to a decrease in mucociliary clearance